Pengaruh Pemberian Petrhikaphos dan Pupuk Fosfor Terhadap Pertumbuhan dan Produksi Tanaman Kedelai (Glycine max (L) Merril) - Hendy Warsito W; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This study aims to determine the effect of the interaction between the administration of petrhikaphos and phosphorus fertilizer, the single factor of petrhikaphos and phosphorus fertilizer and to get the best dose of petrhikaphos and phosphorus fertilizer on the growth and production of soybean plants (Glycine max (L.) Merril). This research is a factorial experiment arranged according to a Completely Randomized Design (CRD) consisting of two factors. The first factor is the Petrhikaphos Dose (P) which consists of 3 levels, namely: P1 = 12.5 g.kg-1 soybean seeds, P2 = 25 g.kg-1 soybean seeds, and P3 = 37.5 g.kg-1 soybean seed. The second factor is the dose of phosphorus fertilizer (F) which consists of 4 levels, namely: F1 = 0 kg.ha-1, F2 = 50 kg.ha-1, F3 = 100 kg.ha-1, and F4 = 150 kg.ha -1. From these two treatment factors, 12 treatment combinations were obtained and each treatment combination was repeated three times so that there were 36 experimental units. Data obtained from observations were statistically analyzed using variance and further testing using Duncan's multiple range test at 5% level. The parameters observed were plant height, number of branches, number of pods per plant, number of seeds per plant, weight of 100 seeds, and weight of seeds per plant. Based on the results of the research that has been carried out it can be concluded that there is an interaction between the administration of pethrikaphos with phosphorus fertilizer on all observed parameters except on number of branches. Giving pethrikaphos 25 g.kg-1 seed showed the best results on all observed parameters. The application of 50 kg.ha-1 phosphorus fertilizer showed the best results on all observed parameters except the number of branches. Giving Pethrikaphos 25 g.kg-1 seed with 50 kg.ha-1 phosphorus fertilizer is the dose that shows the best results compared to other treatments.Keywords: soybean, pethrikaphos, phosphorus, growth and production